Reducing citrus effluent toxicity: Biological-electrochemical treatment with diamond anode - Vilar, Débora S.; Correia da Silva, Hugo H.; Dória, Aline R.; Torres, Nádia H.; Vallim, José H.; Salgado de Castro, Vera L.S.; Américo-Pinheiro, Juliana Heloisa Pinê [UNESP]; Salazar-Banda, Giancarlo R.; Barrios Eguiluz, Katlin I.; Ferreira, Luiz Fernando R. (Elsevier, 2024)
One challenge of the citrus industry is the treatment and disposal of its effluents due to their high toxicity, substantial organic load, and consequent resistance to conventional biotechnological processes. This study introduces a novel approach, using electrochemical oxidation with a boron-doped diamond anode to efficiently remove organic compounds from biodegraded pulp wash (treated using the fungus Pleurotus sajor-caju.) The findings reveal that employing a current density of 20 mA cm−2 achieves notable results, including a 44.1% reduction in color, a 70.0% decrease in chemical oxygen demand, an 88.0% reduction in turbidity, and an impressive 99.7% removal of total organic carbon (TOC) after 6 h of electrolysis. The energy consumption was estimated at 2.93 kWh g−1 of removed TOC. This sequential biological-electrochemical procedure not only significantly reduced the mortality rate (85%) of Danio rerio embryos but also reduced the incidence of morphologically altered parameters. Regarding acute toxicity (LC50) of the residue, the process demonstrated a mortality reduction of 6.97% for D. rerio and a 40.88% lethality decrease for Lactuca sativa seeds. The substantial reduction in toxicity and organic load observed in this study highlights the potential applicability of combined biological and electrochemical treatments for real agroindustrial residues or their effluents.
Keywords: Boron-doped diamond; Ecotoxicity; Electrochemical oxidation; Pulp wash; Sequential treatment